PERFORMANCE OF DIFFERENT GROUNDNUT (Arachis hypogaea L.) VARIETIES AND ECONOMICS UNDER DIFFERENT IRRIGATION SCHEDULES - SK. CHANDINI*; N. VENKATA LAKSHMI; M. SREE REKHA; M. RAVI BABU (The Journal of Research ANGRAU, 2023)
The field experiment was conducted during rabi season of 2021-22 at Agricultural College, Bapatla to evaluate the influence of irrigation schedules on yield and economics of different groundnut varieties. The experiment was laidout in split-plot design and replicated thrice. The experiment consisted of three irrigation schedules viz., IW/CPE ratio of 1.0 (M1), IW/CPE ratio of 0.8 (M2) and IW/CPE ratio of 0.6 (M3) as main plots and four groundnut varieties i.e., TAG-24 (V1), Dheeraj (V2), Kadiri Leapskhi (V3) and Kadiri Chitravati (V4) in sup plots. The results revealed that IW/CPE ratio of 1.0 produced significantly higher pod yield (3175 kg ha-1) and haulm yield (4291 kg ha-1) over IW/CPE ratio of 0.6 but it was at par with IW/CPE ratio of 0.8. Among the varieties tested, highest pod and haulm yield was recorded with Kadiri Lepakshi (3607 kg ha-1) which was significantly superior over Kadiri Chitravati, Dheeraj and TAG-24. Highest gross returns, net returns and returns per rupee invested were obtained with IW/CPE ratio of 1.0 with Kadiri Lepakshi variety when compared to other treatments